HYDROGEN WATER - HOW HEALTHY IS IT? - Mikołaj Daniluk,; Urszula Gadomska,; Natalia Dejewska,; Jowita Wiktoria Maksymiuk,; Zuzanna Walewska,; Mateusz Onopiuk,; Szymon Klimaszewski,; Zuzanna Wiktoria Szumska,; Jonasz Żuk,; Kinga Bukała,; Aleksandra Król, (International Journal of Innovative Technologies in Social Science, 2026)
Hydrogen-rich water (HRW) has recently gained attention as a potential therapeutic modality in health and wellness.H2 is postulated to possess antioxidant properties that can neutralize free radicals in the human body and the evidence suggests that ROS are related to diverse abilities of cancer cells: increased cell proliferation, DNA synthesis, survival, cellular migration, invasion, tumor metastasis, and angiogenesis (Xiao & Miwa, 2017).The potential benefits of hydrogen-rich water have been investigated for liver function, cardiovascular disease, mental health, and oxidative stress. After applying predefined search criteria, numerous relevant publications addressing these aspects were reviewed.Preliminary findings from clinical trials and experimental studies are promising; furthermore, its favorable safety profile, low cost, and ease of administration make hydrogen-rich water an attractive candidate for future preventive and therapeutic applications.  However, further research involving larger cohorts and more rigorous methodologies is required to validate these results. Additionally, the underlying mechanisms responsible for the observed effects of hydrogen-rich water remain to be fully elucidated.